Competencies and Institutions Fostering High-growth Firms - Magnus Henrekson; Dan Johansson (Research Institute of Industrial Economics (IFN), 2008)
High-growth firms (HGFs) are critical for net job creation and economic growth. We analyze HGFs using the theory of competence blocs, linking firm growth to property rights and the interaction of complementary expertise. Specifically, we discuss how the institutional framework affects the prevalence and performance of HGFs. Firm growth is viewed as resulting from the perpetual discovery and use of productive knowledge. A key element in this process is the competence bloc, a nexus of economic actors with complementary competencies that are vital in order to generate and commercialize novel ideas. The institutional framework determines the incentives for these individuals to acquire and utilize knowledge. We identify a number of institutions that foster the emergence of competence blocs and the creation of HGFs. In particular, our analysis points to the pivotal roles played by tax structures, labor market regulation, and the contestability of currently closed service markets. Finally, we characterize institutions beneficial for sclerotic or dynamic capitalism, respectively, depending on whether they provide a favorable environment for the emergence of competence blocs and the creation of HGFs.
Keywords: H32; L25; L50; M13; O31; P14; 330; Competence Bloc; Dynamic Capitalism; Entrepreneurship; Flyers; Gazelles; High-growth Firms; Industrial Policy; Innovation; Institutions; Labor Security; Product Market Regulations; Property Rights; Sclerotic Capitalism; Self-employment; Tax Policy; Unternehmenserfolg; Industriepolitik; Innovation; Eigentumsrecht; Institutionelle Infrastruktur; Steuerpolitik; Schweden